THROMBOCYTOPENIA IN DENGUE HAEMORRHAGIC FEVER - Sutirta-Yasa, I Wayan Putu; Tirta Putra, Gede Agus Eka; Rahmawati, Ana (Medicina, 2013)
The incidence and geographical distribution of dengue has gradually increased during the past decade. Today, dengue is considered one of the most important arthropod-borne viral diseasases in humans in term of morbidity and mortality. Dengue infection   a potential life-threatening dengue hemorrhagic fever (DHF) / dengue shock syndrome(DSS), characterized by thrombocytopenia and increased vascular permiability. Thrombocytopenia causes bleeding, but in   DHF patients with thrombocytopenia do not always develop bleeding manifestation. The pathogenesis of thrombocytopenia are not cleared. Multiple factors  may be involved in the machanisms leading to thrombocytopenia in DHF/DSS patients.
Keywords: dengue hemorrhagic fevers, dengue shock syndrome, thrombocytopenia